Zeolites: A series of promising biomaterials in bone tissue engineering - Li, Yue; Cai, Yanting; Chen, Tianyan; Bao, Xingfu (Frontiers in Bioengineering and Biotechnology, 2022)
As an important worldwide medical issue, bone defect exhibits a variety of physical and psychological consequences on sufferers. Some features of clinical treatments including bone grafting and limb shortening are not satisfactory. Recently, bone tissue engineering has been considered as the most effective approach to dealing with the issue of bone deformities. Meanwhile, a variety of biomaterials have been rationally designed and created for the bone regeneration and tissue repairing. Among all these admirable biomaterials for bone remodeling, zeolite-based materials can serve as efficient scaffold candidates with excellent osteo-inductivity. In addition, the porous nature and high biocompatibility of zeolites endow them with the ability as ideal substrates for cell adhesion and proliferation. More importantly, zeolites are investigated as potential coating materials for implants because they have been proven to increase osteo-conductivity and aid in local elastic modeling. Last but not least, zeolites can also be used to treat bone disorders and act as dietary supplements during the practical applications. Accordingly, numerous benefits of zeolite prompt us to summarize their recent biomedical progress including but not limited to the distinguishing characteristics, broad classifications, as well as promising usages in bone tissue engineering.